Economic evaluation of simulated and traditional clinical placements in occupational therapy education. (25th January 2019) - Gospodarevskaya, Elena; Carter, Rob; Imms, Christine; Chu, Eli Mang Yee; Nicola‐Richmond, Kelli; Gribble, Nigel; Froude, Elspeth; Guinea, Stephen; Sheppard, Loretta; Iezzi, Angelo; Chen, Gang
Abstract : Introduction: This economic evaluation complements results of the randomised controlled trial that established non‐inferiority of the learning outcomes of a one‐week simulated clinical placement (SCP) in occupational therapy qualifying degrees in comparison to an equivalent traditional clinical placement (TCP). This companion study presents detailed cost analyses of two placement alternatives and a cost‐benefit study to assess the value for money of SCP. An economic evaluation of simulated versus traditional placements has not previously been conducted in Australia. Methods: Nine SCP/TCP rounds were conducted by six Australian universities. Costs were collected using study‐specific instruments. Public health sector costs were sourced from available literature. Willingness‐to‐pay for SCP/TCP was estimated using both a Discrete Choice Experiment and a Contingent Valuation method. These methods were employed to assess a comparative 'value' of SCP/TCP from the perspective of heads of occupational therapy departments ( N = 28), who were asked to put a monetary value on the broader range of benefits associated with SCP/TCP. Results: From the universities' perspective the average cost per student ranged from AUD460 to AUD1511 for simulated and AUD144 to AUD1112 for traditional placement. From the health care sector perspective, the difference in costs favoured simulated placements for four implementations and traditional placements for five. In the Discrete Choice Experiment respondents preferred traditional rather than simulated placement and would pay additional AUD533. The estimated monetary value of simulated placements from a contingent valuation ranged from AUD200 to AUD1600. Conclusions: For universities that procure TCPs predominately at public health care facilities and sustain high administrative overheads, the SCP program could be a cost‐saving alternative. From a broader value‐for‐money perspective, respondents favoured TCP over SCP, yet placed importance on placement availability and opportunity to demonstrate competence for students during the placement. Results should be interpreted with caution and further research with larger sample sizes is required.